The strategy to monetize the waste from cattle livestock in pt. Agrikulture indonesia - Ramadhani, Rezki; Dung Do, Anh (The Indonesian Journal of Business Administration, 2018)
Abstract – PT. Agrikulture Indonesia is a cattle importer and feedlot that is located in Bogor, Indonesia. The company started the business in 2009 by importing cattle from Australia and recently, the feedlot has a capacity of seven thousand cattle. These cattle approximately yield seventy thousand kilograms manure every day and the company processes it into organic fertilizer. However, there is a difficulty in selling this big amount of fertilizer due to the lack of knowledge about the industry. This study attempts to answer three questions, i.e. the fertilizer industry analysis in Indonesia, the alternative solutions for the cattle manure problem in Agrikulture and the strategy for monetizing its waste. In order to answer these questions, the author firstly makes the business situation analysis using external and internal analysis. Secondly, the research methodology is the combination of questionnaire and interview with the related stakeholders in the agriculture industry. Thirdly, the strategy formulation is derived from the Diamond Strategy and TOWS Matrix. Lastly, the strategy formulation that consists of a new business model canvas and strategic control. (i) to continue on selling the fertilizer by improving the fertilizer business unit, and/or (ii) to create a crop farm project together with a strategic partner. The recommended strategy for monetizing the waste in Agrikulture is to create a crop farm project with a strategic partner. By benefiting its economies of scale, Agrikulture can offer low price product in bulk quantity. The company should prioritize the crops that can be benefiting its cattle feedmill and reduce its food cost in the future. The strategic partner is very important for Agrikulture to minimize the project cost and risk.